(untitled) (Bangladesh Journal of Medical Science, 2025)
Aim Surgical site infections (SSIs) are a common and significant complication following surgery. This study aimed to evaluate the prevalence of SSIs, investigate associated risk factors and comorbidities, and assess the impact of antibiotics on their occurrence among patients treated at Hargeisa Group Hospital. Methods Conducted as a cross-sectional study at Hargeisa Group Hospital, Somaliland, 113 patients were selected randomly from 314 surgical cases between May 1 and July 31, 2022. Data analysis was performed using SPSS software. Results Among the 97 patients included, 50 were female (51.5%) and 47 were male (48.5%). The prevalence of SSIs was 27% (26 patients). Among these, 65% (17 patients) had superficial infections, 23% (6 patients) had deep infections, and 3 patients experienced organ space infections. The study identified a significant relationship between health status and SSIs, with ASA II patients showing a prevalence of 23.1% compared to 50% in ASA I patients. Diabetes was the most frequent comorbidity, observed in 6 (23.1%) SSI patients compared to 10 (14.1%) non-SSI patients. Antibiotic prophylaxis was provided to 18 (69.2%) of SSI patients, while 21 (29.6%) of non-SSI patients did not receive antibiotics, with a statistically significant p-value of 0.001. Conclusions SSIs remain a prevalent issue globally. This study identified a 27% prevalence rate, with diabetes as the most common comorbidity in affected patients. BJMS, Vol. 24 No. 04 October’25 Page : 1124-1130